An Appraisal on Usage of the term “Aḥl al Ḥadīth” in Formative Islamic Period and its extended meanings in Later Centuries in Indian Subcontinent: A Historical Review - Al Ghouri, Syed Abdul Majid (Journal of Islamic and Religious Studies, 2020)
In the early Ḥijrī centuries, the title Aḥl al-Ḥadīth was given various Islamic groups having different inclinations of religion, fiqh-following (Madhahib) and scholarly pattern which was used by a specific group of the subcontinent in later centuries. This caused great confusion in understanding the intended meaning of this title and difference between the past and present groups to the scholars. Hence, the paper looks into the intended meaning in the early history of Islam in light of statements of authentic scholars, and then introduces those people who were associated with this title in the Indian sub-continent in the later century, and highlights the determining differences between this contemporary reference to its earlier use. The paper divides the contents into two sections: firstly, it explains the intended meaning of Aḥl al-Ḥadīth in the early Ḥijrī centuries, secondly, it focuses on introducing those who were associated with this title in the Indian subcontinent whether by theological or fiqh-following. Moreover, the paper highlights the areas of theological similarity between this group and the Salafī group due to a claim made by the later that they belonged to the prior and have the ideological and theological roots.